PENGARUH INISIASI MENYUSU DINI (IMD) DAN FAKTOR SOSIAL DEMOGRAFI TERHADAP KETAHANAN PEMBERIAN ASI EKSKLUSIF - Mumpuni, Retno Sari; Utami, Efri Diah (E-Journal Widya Kesehatan dan Lingkungan, 2018)
Abstrac:t: The Indonesia’s Infant Mortality Rate (IMR) experienced a downward trend. However, within the last 10 years the decline was only 3 deaths out of 1.000 live births. One of the efforts to reduce the risk of infant mortality were taken is a program of the National Movement Increased use of Breast Milk. Breast milk is an important food that should be given to a baby especially in the early days of the birth. The results of the SDKI (2012) indicate that from 96% of the breast milk fed babies, only 42% who are exclusively breastfeeding. According to UNICEF, one of the 10 steps to success breastfeeding are given Breast immediately after the baby birth (Early Initiation of Breastfeeding). The purpose of this research is to determine the influence of the early initiation of the breastfeeding and social demographic factors against the resilience of the Exclusive breastfeeding in Indonesia. The results of this study showed that infants who received IMD in more than an hour after birth has 1.661 times greater risk for not exclusively breastfed compared to infants who were breastfed within the first hour after birth. While socio-demographic factors that influence the resilience of exclusive breastfeeding is parity, Early Initiation of Breastfeeding (IMD) and employment status of the mother.